2009
DOI: 10.1097/mnm.0b013e32832bdcac
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dual-time-point 18F-FDG-PET imaging for pulmonary lesions

Abstract: It is recommended that dual-time-point 18F-FDG-PET imaging is not indicated to differentiate between malignant and benign pulmonary lesions, whose size and maximal SUV are greater than 10 mm and 2.5, respectively. Furthermore, a model analysis suggests that the variation in SUV observed between early and delayed scans may be explained by different values of the 18F-FDG release/uptake ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 15 publications
0
20
0
3
Order By: Relevance
“…Recently, similar to the present study, Laffon et al [29] conducted a study to assess suitability of dual-time-point 18 F FDG PET imaging for differentiating between malignant and benign pulmonary lesions. In their study, they recommended that dual-time-point 18 F FDG PET imaging is not indicated to differentiate between malignant and benign pulmonary lesions.…”
Section: Discussionmentioning
confidence: 52%
“…Recently, similar to the present study, Laffon et al [29] conducted a study to assess suitability of dual-time-point 18 F FDG PET imaging for differentiating between malignant and benign pulmonary lesions. In their study, they recommended that dual-time-point 18 F FDG PET imaging is not indicated to differentiate between malignant and benign pulmonary lesions.…”
Section: Discussionmentioning
confidence: 52%
“…For example, differentiation between malignant and inflammatory lesions was not consistently successful using DTPI because some studies have shown nonspecificity in lung and mediastinal lesions and lung nodules with low FDG uptake. 42,66,68,69,[87][88][89] In addition, acute infectious and noninfectious inflammatory lesions, specifically granulomatous lesions, show a pattern similar to the malignant lesions 90,91 and therefore DTPI is not considered to be superior to STPI in the areas with high prevalence of sarcoidosis and in tuberculosis (TB)-endemic areas. 42,66,68,69,88,89,92 However, DTPI is still a useful option for differentiation of inactive granulomatous or chronic inflammatory lesions from malignancy because of difference in the biological behavior of the cells involved in the chronic versus acute inflammation.…”
Section: Challenges Summary and Future Directionsmentioning
confidence: 96%
“…6-9) with some limitations reported in the literature, including false-positive and false-negative results. 4,5,42 However, over delayed times of 2 or 3 hours, the lymph nodes become clearer and easier to detect compared with 1-hour imaging.…”
Section: Applications Of Dual-time-point Imaging In Malignant Diseasementioning
confidence: 98%
“…35 Ten publications 28,29,31,33,34,[36][37][38][39][40] fulfilled all of the inclusion criteria, with a total of 816 patients and 890 pulmonary nodules. Multiple different thresholds were used to define a pulmonary nodule as malignant between the initial and later images.…”
Section: Lung Cancermentioning
confidence: 99%